Phasor [compact disc] - Helado Negro, 1980- (4AD, 2024)
While Phasor feels loose and expansive, it's Lange's tightest collection, deep, atmospheric, meticulously executed. It's aligned with 2019's This Is How You Smile, which found him incorporating more upfront drums and bass and focused grooves. Sequentially, it follows the expansive hour-plus long Far In, whose title was inspired by new age legend Laraaji and created in lockdown, in Marfa, Texas, lyrically digging into connection and focused on being in quarantine. Phasor, in turn, is an homage to going outside again. It's a returning-to-life record, remembering what the sun feels like and letting it warm your skin.